Over-expression of Nectin-4 promotes progression of esophageal cancer and correlates with poor prognosis of the patients - Haifeng Deng; Hongbing Shi; Lujun Chen; You Zhou; Jingting Jiang (2019)
Nectin-4, also known as PVRL4 (poliovirus-receptor-like 4), is specifically expressed in the embryo and placenta. Recent studies have reported that the Nectin-4 is over-expressed in multiple human cancers, and such abnormal expression is associated with cancer progression and poor prognosis of the patients. In the present study, we aimed to characterize the expression pattern of Nectin-4 in human esophageal cancer (EC) tissues, and to investigate its clinical implications, prognostic value and regulatory effects on cellular functions of EC cells. In the present study, we first examined Nectin-4 expression in human EC tissues by using immunohistochemistry (IHC) assay and analyzed the clinical associations. Then the cellular studies in vitro and the nude mice tumor model in vivo were used to examine the regulatory role of Nectin-4 in the progression of EC. Our results demonstrated that over-expression of Nectin-4 in human EC tissues was significantly associated with tumor size, depth of tumor invasion, and poor prognosis of the patients. The intervention of Nectin-4 expression in EC cell lines showed that the increased Nectin-4 expression could significantly promote the cell viability, migration, invasion and tumor formation. Our present data unveiled that Nectin-4 played an important role in tumor biology and could serve as a useful prognostic predictor of human EC.